2007
DOI: 10.1016/j.physbeh.2006.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of food reward by adiposity signals

Abstract: Extensive historical evidence from the drug abuse literature has provided support for the concept that there is functional communication between central nervous system (CNS) circuitries which subserve reward/motivation, and the regulation of energy homeostasis. This concept is substantiated by recent studies that map anatomical pathways, or which demonstrate that hormones and neurotransmitters associated with energy homeostasis regulation can directly modulate reward and motivation behaviors. Studies from our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 58 publications
3
123
1
Order By: Relevance
“…However, there is also a hedonic aspect to feeding and hedonic feeding will possibly involve dopaminergic mechanisms of reward [152,[361][362][363][364]. A functional link between hypothalamic energy-control mechanisms and the motivational aspect of feeding has been demonstrated by Helm et al [240].…”
Section: Serotonin and The Pharmacotherapy Of Obesitymentioning
confidence: 99%
“…However, there is also a hedonic aspect to feeding and hedonic feeding will possibly involve dopaminergic mechanisms of reward [152,[361][362][363][364]. A functional link between hypothalamic energy-control mechanisms and the motivational aspect of feeding has been demonstrated by Helm et al [240].…”
Section: Serotonin and The Pharmacotherapy Of Obesitymentioning
confidence: 99%
“…This system is responsive not only to a variety of glutamatergic inputs from local (Dobi et al, 2010) and distal (Geisler et al, 2007) neuronal sources, but also to a number of state variables mediated by blood-borne factors including leptin (Figlewicz et al, 2003;Krugel et al, 2003;Hommel et al, 2006;Liu et al, 2011;Thompson and Borgland, 2013). Leptin is an endogenous inhibitor of food reward (Figlewicz et al, 2007;Domingos et al, 2011) that has both direct (Fulton et al, 2006a;Krugel et al, 2003;Leinninger et al, 2009;Davis et al, 2011;Domingos et al, 2011) and indirect (Leinninger et al, 2009) effects on brain reward function and that is depressed in heroin addicts (HousovĂĄ et al, 2005) and fluctuates abnormally during craving for alcohol (Kiefer et al, 2005) or nicotine (al 'Absi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relative paucity of available data in humans (Benedict et al, 2008;Hallschmid et al, 2012;Jauch-Chara et al, 2012) and animals (Woods et al, 1979;McGowan et al, 1992;Air et al, 2002;Clegg et al, 2003Clegg et al, , 2006 at the moment does not permit sound conclusions on macronutrient-specific effects of brain insulin on eating behavior (for review see Kullmann et al, 2016;Lee et al, 2016). Animal research has indicated that the adiposity signals insulin and leptin can directly act on the brain reward circuitry to decrease the intake of particularly palatable foods (Figlewicz et al, 2007). Although at a first glance, the insulin-induced reduction in carbohydrate intake would fit with the assumption that intranasal insulin specifically reduces the intake of highly rewarding foods , sweet items as a food category were not differentially affected here.…”
Section: Discussionmentioning
confidence: 99%